Coupled High Spin CoII Ions Linked by Symmetrical Double Hydrogen Bonds: Role of a Slowly Relaxing CuII Impurity in Interrupting the CoII–CoII Exchange Interaction - Pérez, Ana Laura (2018)
CoII and CuII ions are two paramagnetic transition metal ions showing different relaxation rates (ν), with νCo II >> νCu II. To measure the isotropic exchange constant (J) between high spin CoII ions and between CuII ions and high spin CoII ions, we performed magnetic and EPR measurements complemented with computational calculations on pure trans-diaqua-bis(picolinato-N,O)-cobalt(II) dihydrate (1), on the CuII ion doped compound of 1 (2), and on the CuII ion doped compound in a ZnII matrix isomorphous to 1. The temperature dependence of the CuII EPR resonance lines of 2 induced by the fast relaxing CoII ion host as well as the evaluation of the temperature-independent CoII?CoII and CuII?CoII isotropic exchange interaction are analyzed. We determined an antiferromagnetic interaction [JCo?Co = ?1.07(1) cm?1] associated with a double symmetrical hydrogen bond bridge and another one [|J|Co?Cu = 0.0015(2) cm?1] associated with a double but asymmetrical hydrogen bond bridge, which are in line with the values obtained from computational calculations. This work shows that EPR spectroscopy can advantageously be used to evaluate weak exchange interactions between distinct metal ions with different relaxation rates by using the fact that those metal?metal interactions that broaden the EPR resonance line, which are described by matrices with a trace of zero, are averaged out at high temperatures.